2003
DOI: 10.1002/ajmg.a.20241
|View full text |Cite
|
Sign up to set email alerts
|

Rib defects in patterns of multiple malformations: A retrospective review and phenotypic analysis of 47 cases

Abstract: Rib anomalies may occur in isolation, as well as in association with abnormalities of vertebral segmentation and multi-system malformations. Specific entities include the VACTERL and MURCS associations, spondylocostal dysostosis, and spondylothoracic dysostosis. The relative significance of rib anomalies in other lesser known syndromes and associations remains unclear. To document the diagnoses and related defects in patients with rib anomalies as part of broader pattern of anomalies, we retrospectively identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 26 publications
(24 reference statements)
1
41
3
2
Order By: Relevance
“…It has been reported that rib fusion is the most common type of rib anomaly in association with other congenital malformations [23]. The fact that an NTD develops in the first 4 weeks and rib development begins not sooner than week 9 of gestation [24] explains why we only found a rib missing in 390 patients of MMC and not rib fusion.…”
Section: Discussioncontrasting
confidence: 40%
“…It has been reported that rib fusion is the most common type of rib anomaly in association with other congenital malformations [23]. The fact that an NTD develops in the first 4 weeks and rib development begins not sooner than week 9 of gestation [24] explains why we only found a rib missing in 390 patients of MMC and not rib fusion.…”
Section: Discussioncontrasting
confidence: 40%
“…It has been established that the specific type of rib anomaly can help identify and define associated syndromes or malformations, which will in turn provide the patient with a complete and well-rounded diagnosis. [1] Although bifid rib neither gives rise to severe clinical afflictions nor affects a great proportion of the population, its consideration especially in perspective of associated diseases hasdemonstrated preventative advantages. Early detection and therefore, prevention, is particularly vital in the pediatric patient population as it can possibly reduce the severity of longterm complications of an associated syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…[20] The diseases that have been reported include, but are not limited to: congenital bone dysplasia, acquired metabolic diseases, iatrogenic conditions, neoplasms, vertebral segmentation, spondylocostaland spondylothoracicdysostosis, and thoracic outlet syndrome. [1,20] Other studies have identified additional diseases/malformations that can be associated with bifid rib specifically: deficient lateral clavicle, mandibular hypoplasia, macrocephaly, mental retardation, chest wall tumor, and costal fracture. [4,24] Unlike other rib anomalies, bifid rib usually occurs in the absence of vertebral defects.…”
Section: Symptoms Complications and Case Studiesmentioning
confidence: 99%
“…Non-random associations of birth defects that comprise bifid ribs are VACTERL (vertebral anomalies, anal atresia, cardiovascular anomalies, tracheoesophageal fistula, renal and/or radial anomalies, limb defects), MURCS (Müllerian duct aplasia, renal aplasia, and cervico-thoracic somite dysplasia) [15]. A single bifid rib is most commonly a normal incidental finding and may be detected as a palpable chest wall mass; it is usually considered a normal anatomic variant and it's often asymptomatic.…”
Section: Discussionmentioning
confidence: 99%